How to do everything with Adobe Acrobat 5.0 - Sahlin, Doug (McGraw-Hill/Osborne, 2002)
Sahlin provides the user with concise information about getting the most from all aspects of Adobe Acrobat version 5.0. It features hands-on examples of how the software provides unique solutions to real-world problems.